Impacts of inter-train distances on aerodynamic drag reduction in heavy-haul train groups - LYU Jun; XIANG Tao; SONG Zongying; GAO Guangjun (机车电传动)
The operation of trains in groups at short distances represents a potential trend for the future development of heavy-haul railway transport. This paper analyzes the impacts of inter-train distances in this operational mode on the aerodynamic characteristics of trailing trains, using computational fluid dynamics (CFD) methods, based on the SST k-ω turbulence model. Initial algorithm validation was performed, and the results were compared with data from wind tunnel experiments conducted in a large low-speed wind tunnel at the China aerodynamics research and development center. The comparison indicated an error of 3.4%, suggesting a close alignment between the numerical simulation data and the results from the wind tunnel experiments. In the subsequent grid independence verification, three gridding methods were selected for simulations: coarse, medium, and fine grids. Apparent errors were observed in the coarse grid configuration, while variations in aerodynamic drag acting on the whole train were less than 3% for the medium and fine grids. Therefore, the latter two levels of grid accuracy were considered conforming to simulation calculation requirements, making the corresponding results reliable. Further numerical simulations and analyses were conducted, using two heavy-haul trains at six different spacings. The study revealed that as the inter-train distance decreased, the aerodynamic optimization effect from the leading train on the trailing train gradually became apparent, with the overall aerodynamic drag coefficient of the trailing train decreasing by up to 16%. Specifically, the drag reduction rate for the locomotive reached 17%, and that for the trailers was 14%. The main reason for drag reduction was identified as the low-speed wake zone formed at the rear of the leading train. Comparisons at different inter-train distances showed that the drag reduction effect was minimal at distances greater than 700 meters, while no significant improvement in drag reduction effect was observed at distances less than 200 meters. In summary, optimization of aerodynamic characteristics for trailing trains in group operation occurs at spacings of less than 700 meters, achieving the optimal drag reduction effect when the spacing is reduced to 200 meters.